Biologically potent organotin(iv) complexes of N-acetylated β-amino acids with spectroscopic, X-ray powder diffraction and molecular docking studies. Issue 16 (5th April 2023) - Riaz, Nagina Naveed; Ahmed, Muhammad Mahboob; Kashif, Muhammad; Sajid, Muhammad; Ali, Muhammad; Mahmood, Khalid
Abstract : Novel organotin(iv ) complexes of N -acetylated β-amino acids were synthesized and characterized by different techniques. The molecular docking, in vitro α-glucosidase inhibitory, and in vivo antidiabetic activity studies were carried out. Abstract : Twelve novel organotin(iv ) complexes (1–12 ) of N -acetylated β-amino acids (L1 –L8 ) were synthesized and characterized by elemental analysis, FTIR, multinuclear ( 1 H, 13 C, 119 Sn) NMR, EI-MS and powder XRD techniques. The XRD results determined lattice parameters, average particle size, and intrinsic strain and confirmed the crystalline nature of complexes as face centered cubic phases. Molecular docking analysis using a catalytic pocket of the α-glucosidase enzyme indicated that most of the compounds displayed a well-fitted orientation and occupied important amino acids in the enzyme's catalytic pocket. Furthermore, in vitro α-glucosidase inhibitory activity results revealed that L1 and complexes 4, 6 and 10 showed the highest activity with IC50 values of 21.54 ± 0.45, 37.96 ± 0.81 and 35.20 ± 1.02, respectively, compared to standard acarbose with an IC50 value of 42.51 ± 0.21. In addition, in vivo antidiabetic activity of selected compounds using alloxan induced diabetic rabbits showed that L4 and complexes 4, 6, 10, 12 showed significant activities like standard metformin. Anti-bacterial activity against the selected Gram-positive and Gram-negative bacterial strains has the following order Escherichia coli > Pseudomonas aeruginosa > Staphylococcus aureus > Bacillus subtilis . Similarly, antioxidant activity by the DPPH scavenging method was also studied with following results: triorganotin > diorganotin > ligands.